A Study To Investigate Expressions Of Faulty Gene That Cause Disease. Several Types Of Inherited Diseases May Be Completely Cured If Detected And Treated Early Enough - DAI YongXia; NURUL AZMIR BIN AMIR HASHIM; SURIYAKALA (Revista Electronica de Veterinaria, 2024)
Many genes and environmental factors often work together to cause a disease. The identification of significant genetic factors is useful for both medical (by aiding drug development and personalised therapy) and scientific (by shedding light on mechanistic and evolutionary aspects of illness) purposes. Linkage analysis (which joins loci that have a propensity to be inherited together) and association studies are two of the many genetic methods that have shown correlations between illnesses and particular sections of the genome (mapping correlation between alleles at different loci). Several hundreds of genes are examined in these types of studies, much too numerous to be tested experimentally as potential disease genes. The use of computer methods to assess the possibility of individual genes within a certain chromosomal area being disease genes is thus quite useful. Many diseases' susceptibilities have been demonstrated to a fair degree. changes in the rate at which genes are expressed in various cell types. In instance, if a gene or gene cluster is more common in sick individuals than in healthy people, it's likely that the gene plays a role in illness. Microarray studies were the major method for detecting the differences in expression levels.